2020
DOI: 10.1038/s41598-020-65848-7
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of ELISA and Lateral Flow Kits for rapid Diagnosis of Mycoplasma gallisepticum in Poultry

Abstract: Avian mycoplasmas were mainly the cause of poultry industry economic losses; reduced meat and egg production and increases the antibiotic treatment cost. Mycoplasma gallisepticum (MG) infection is designated as infectious sinusitis of turkeys and chronic respiratory disease of chickens (gasping, depression, semi closed eyes, infraorbital sinuses edema and decrease in egg production). This study aimed to prepare, evaluate and Compare in-house ELISA kits and lateral flow assay (LFA) from a local strain of MG wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The evaluation of the relative specificity, sensitivity, and accuracy for LFIT using P04310-10 IDEXX brucellosis ovine/caprine Ab ELISA test (gold standard) was performed, and the results of sensitivity, specificity, and accuracy of LFIT and Rose Bengal test were compared with those of ELISA and found to be 74%, 89%, and 81% and 59%, 76.9%, and 66%, respectively. A nearly similar result was obtained by Elyazeed et al [27], who found that the LFIT had low sensitivity with high specificity (77.5% and 92%), respectively, for the detection of Mycoplasma gallisepticum. For the detection of brucellosis, the sensitivity and specificity were recorded as 78.57% and 93.07%, respectively [28].…”
Section: Discussionsupporting
confidence: 84%
“…The evaluation of the relative specificity, sensitivity, and accuracy for LFIT using P04310-10 IDEXX brucellosis ovine/caprine Ab ELISA test (gold standard) was performed, and the results of sensitivity, specificity, and accuracy of LFIT and Rose Bengal test were compared with those of ELISA and found to be 74%, 89%, and 81% and 59%, 76.9%, and 66%, respectively. A nearly similar result was obtained by Elyazeed et al [27], who found that the LFIT had low sensitivity with high specificity (77.5% and 92%), respectively, for the detection of Mycoplasma gallisepticum. For the detection of brucellosis, the sensitivity and specificity were recorded as 78.57% and 93.07%, respectively [28].…”
Section: Discussionsupporting
confidence: 84%
“…Mycoplasmas are small prokaryotes that lack a cell wall, but they are surrounded by 3 layers of the plasma membrane, 300 to 800 nm in diameter. It can be detected in humans and animals, with an optimum growth temperature of 37°C with the ability to replicate outside of host cells ( Brown et al., 2007 ; Abdel Halium et al., 2019 ; Abo Elyazeed et al., 2020 ; Sawicka et al., 2020 ). Mycoplasma gallisepticum is the most virulent and economically significant bacterial respiratory infection of poultry.…”
Section: Introductionmentioning
confidence: 99%
“…The sample is placed on the testing device, and results are displayed within 5-30 minutes, making it easy to detect specific analytes in fluids or other samples (Gao et al, 2018;Koczula and Gallotta, 2016). Elyazeed et al (2020) conducted a study to develop, assess, and compare LFAs with commercial ELISA kits and PCR methods. The research indicated that lateral flow assays demonstrated lower sensitivity compared to PCR but higher specificity.…”
Section: Lateral Flow Immunochromatographic Analysismentioning
confidence: 99%